Identification of yield-related QTLs and their applications using DH population in maize - Yifei Wang; Dongxu Yao; Junfeng Song; Xiaochun Zhang; Yanbin Zhu; Zhichun Luo; Jinsheng Lai; Weibin Song; Tianxia Yang (BMC Genomics)
Abstract Background Kernel row number (KRN) and ear length (EL) are key traits that contributes greatly to grain yield in maize (Zea mays L.). Although some quantitative trait loci (QTL) for KRN or EL have been identified, few have been effectively utilized in breeding. Results In this study, we identified QTLs for maize KRN and EL using biparental (PHBA6 and Chang7-2) maize DH populations in 4 environments, and a total of 9 consensus QTLs were identified, including 6 KRN QTLs and 3 EL QTLs, of which 3 consensus QTLs were novel. By integrating genome-wide association studies (GWAS), transcriptomic and gene sequence analysis, we identified 3 candidate genes in the new consensus QTLs. Among these, Zm00001d031913 (WAT1-related protein) and Zm00001d026621 (WD40 protein), parental homologous genes showed structural variations (SVs) in the promoter region, and the Coding Sequence (CDS) have amino acid deletions or substitutions, they are key candidate genes for KRN. Further, we identified and validated an excellent breeding selection signal, the qEL3.1 genotype of PHBA6, which successfully increased EL in the Zhengdan958, a widely cultivated commercial hybrid. Concurrently, we observed a reduction in ear height (EH), which is also a favorable phenotype in maize. Conclusions Our work providing valuable insights for targeted genetic improvements and enhances the understanding of the genetic basis of KRN and EL in maize.